Optimization of cycling properties of the layered lithium cobalt nitride Li2.20Co0.40N as negative electrode material for Li-ion batteries. (10th June 2015) - Ducros, J.B.; Bach, S.; Pereira-Ramos, J.P.; Willmann, P.
Abstract: An optimization of the specific capacity exhibited by the best layered lithiated cobalt nitride Li2.20 Co0.40 N is proposed by using a conditioning electrochemical oxidation up to 1.1 V before cycling in the 1.1 V–0.02 V potential range. This initial charge process allows the Co 3+ /Co 2+ redox couple to be involved in the cycling process in addition to the Co 2+ /Co + couple as in the 1 V–0.02 V voltage range. A new electrochemical fingerprint is obtained with a single step at 0.4/0.8 V for the discharge-charge process and a specific capacity of 300 mAh g −1 at C/5 which constitutes a huge improvement compared to 130 mAh g −1 recovered in the conventional 1 V–0.02 V potential window. This high capacity value and the excellent capacity retention of 100% over at least 75 cycles make Li2.20 Co0.40 N a promising anode material for Li-ion batteries.